Corporate Social Responsibility vs. Business Strategy - Aluchna M. (Ural State University of Economics, 2018)
The article discusses the concept of corporate social responsibility (CSR) viewed as an important direction for the evolution of business towards low emission and resource efficient business models and responsible and inclusive economy. With the appreciation to the contribution of the concept for social and economic development the goal of the article is to identify the most important concerns and shortcomings rising from of the application of the corporate social responsibility in business strategy. The article is of theoretical character and is based on the review of the recent literature on CSR, sustainability and non-financial reporting. The paper argues that while the CSR concept proposes important rationales for the evolution of business, it may have a limited effect on the factual change with respect to business models and strategy. Specifically, the concept raises several concerns related to the coherence and the clarity of its theoretical approach as well as severe methodological and measurement shortcomings. In addition, corporate social responsibility faces problems of the firm intention and its effective implementation in the organisational context.